Potret Kehidupan Sosial Mahasiswa Pengamen di Kota Gorontalo: Studi Kasus Mahasiswa UNG Asal Kabupaten Buol - Saputra, Gunawan; Rahmatiah; Hatu, Dewinta Rizky R. (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2025)
This study examines the phenomenon of students from Buol Regency who migrate to Gorontalo City and work as buskers to support themselves while pursuing their education at the Universitas Negeri Gorontalo (UNG). The aim of this study is to analyze the social life portrait of busker students, including their motivations, challenges, and interactions with their surrounding environment. The research adopts a descriptive qualitative approach, with data collection techniques involving observation, in-depth interviews, and documentation. The findings indicate that most of the busker students come from families with a lower-middle economic background. The primary factors driving them to busk include economic limitations, the desire for independence, and the outlet for their musical talents. Busking provides them with flexible working hours but is often accompanied by negative stigma from the community. Despite this, they demonstrate strong social resilience and are able to balance their roles as students and income earners. This phenomenon reflects the existence of an educated marginal group that requires attention in social planning and public policy.